Fast-food and obesity: Status among the younger population in Bangladesh - Tareq, Abu M.; Mahmud, Md. Hasan; Billah, Md. Motashen; Hasan, Md. Nazmul; Jahan, Shamima; Hossain, Md. Mohotasin; Chy, Farhana J.; Uddin, Md. Giash; Emran, Talha B.; Sayeed, Mohammed A. (Narra Sains Indonesia, 2022)
Increasing rate of fast-food consumption has been associated with different health related concerns (e.g., obesity, heart disease). This study aimed to determine the prevalence of fast-food consumption among young adult students in Chittagong, Bangladesh, and to assess the correlation of fast-food consumption with obesity. A total of 440 youth was included using a systemic random sampling from universities and colleges in Chittagong in order to perform a cross-sectional analysis. The students who reported frequent fast-food consumption (1–3 times per week) accounted for 30.5% (n=134) of the sample, while 32.5% (n=143) of participants reported consuming fast-food 8–15 times per month. There was a significant (p=0.030) diﬀerence between students who consumed and did not consume fast-food. Youth who reported consuming fast-food and soft drinks more than 4 times per week constituted 35.0% (n=154), followed by approximately 27.7% (n=122) who consumed these items 1–3 times per week. In addition, an obesity epidemic was observed among those who reported low levels of physical exercise or lack of sleep. The study illustrates that Bangladeshi youth face an increasing risk of becoming overweight and obese. Prevention is regarded as the most effective way to reduce the prevalence of obesity.